2017
DOI: 10.5539/gjhs.v9n7p47
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Current and Missing Knowledge in the Control of Pyrethroid-Resistant Triatoma infestans, Vector of Chagas Disease

Abstract: Triatomines are blood-sucking bugs that occur mainly in Latin America. They are vectors of Trypanosoma cruzi, the parasite that causes Chagas disease. Chemical control of Chagas disease´s vectors by using pyrethroid insecticides has been highly successful for the elimination of domestic infestation and consequently the reduction of the vector transmission. However, at the beginning of the 2000s a decrease in the effectiveness of the chemical control of triatomines was detected in several areas from Argentina a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Regarding the resistance mechanism(s) underlying the altered susceptibility patterns in Mat, analyses of P450 monoxygenases and 7-CP esterases (Roca-Acevedo et al, 2011;Roca-Acevedo and Picollo, 2017) showed a lack of association between enzymatic activities and susceptibility ratios, indicating that these enzymes were not responsible for modified susceptibility in these sylvatic populations. In this work, we evaluated the presence of two kdr mutations and found one individual from Mat-S carrying the mutation L1014 (Fabro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the resistance mechanism(s) underlying the altered susceptibility patterns in Mat, analyses of P450 monoxygenases and 7-CP esterases (Roca-Acevedo et al, 2011;Roca-Acevedo and Picollo, 2017) showed a lack of association between enzymatic activities and susceptibility ratios, indicating that these enzymes were not responsible for modified susceptibility in these sylvatic populations. In this work, we evaluated the presence of two kdr mutations and found one individual from Mat-S carrying the mutation L1014 (Fabro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%